TRANSFORMING HIGHER EDUCATION IN MOLDOVA: A JOURNEY THROUGH DIGITALIZATION, AI AND FINANCIAL CONSIDERATIONS - Adrian ANDRONIC (Eastern European Journal of Regional Studies, 2024)
This paper analyzes Moldova's higher education transformation, focusing on digital and AI integration, underpinned by the Moldova Higher Education Project financed by the International Development Association. Findings highlight the project's effectiveness in aligning education with labor market demands through AI-driven personalized learning and administrative automation, significantly enhancing learning environments and operational efficiencies. Challenges include the need for improved digital infrastructure and equitable technology access. The study offers actionable recommendations for policymakers, such as enhanced AI training for educators and policy development to ensure fair access to technology. These insights contribute significantly to understanding and implementing educational reforms in similar contexts.